Education on Disaster Mitigation and Social Participation among Vocational School Students in Pangkep Regency - Kamaruddin, Syamsu (Tamaddun Life, 2023)
Acquiring knowledge about flood mitigation is highly beneficial for students, as it equips them with a valuable skillset to assist others. This study aims to achieve the following objectives: (1) Evaluate the delivery of flood disaster mitigation education among students of SMK Muhammadiyah Pangkep Regency. (2) Examine the impact of disaster mitigation knowledge on the level of social engagement among students at SMK Muhammadiyah Pangkep Regency. The research methodology employed is quantitative, utilizing a survey-based technique. The study was conducted in SMK Muhammadiyah Pangkep Regency. The study population consisted of vocational students, and a stratified selection procedure was employed to choose a sample of 67 individuals from class IX and class X. The data collection methodology employed questionnaires and document analysis. Methods of data collecting involving the use of surveys and the examination of documents. Data processing techniques involve the manipulation and organization of data, whereas data analysis refers to the examination and interpretation of data. In this case, frequency tabulation using percentage approaches is used to analyze the data, and the results are described in a descriptive manner. The study found that the instruction on flood disaster mitigation implemented in students of SMK Muhammadiyah Pangkep Regency was in line with the teaching guide. (2) Disaster mitigation knowledge has a positive influence on the level of social participation among students of SMK Muhammadiyah Pangkep Regency, as it equips them with the necessary information and abilities to assist others. Students have encountered floods, and the skills and knowledge they acquired have enhanced their understanding of flooding. These consequences highlight the necessity for customized and community-led tactics in managing disasters, ultimately leading to a community that is more resilient and prepared for disasters.